NUMERICAL ANALYSIS OF DIFFERENT CONFIGURATIONS OF A COMPLEX COMMERCIAL SINK SUBJECTED TO FORCED CONVECTIVE TURBULENT FLOWS - Melo Claudino, Tarciso; Franz Zauk, Otávio; André Isoldi, Liércio; Alberto Oliveira Rocha, Luiz; Liles Jorge Drews Junior, Paulo (Revista de Engenharia Térmica, 2025)
The compactness of electronic packaging embarked in autonomous drones associated with the increase of processing capacities of the electronic compounds has increasing their heat generation per unit volume. Moreover, the control of temperature is a chief aspect to ensure the life cycle of the electronic packaging of the drone. The present work has the purpose to perform a numerical investigation of a commercial heat sink with complex configuration subjected to turbulent, incompressible, three-dimensional, and forced convective flow. Different geometric configurations are investigated seeking to obtain a theoretical recommendation about the influence of the geometry over the heat transfer rate between a commercial sink (NVIDIA Jetson NanoTM) and the turbulent forced convective flow. The sink simulated is used for cooling the electronic components of a microcomputer used in autonomous unmanned aerial vehicle (UAV). More precisely, it was investigated four different configurations of one fin of the sink with different positions (defined by the ratio between the distance of intermediate fin to the center of sink and the total length of the sink, L1/L) and different inclination angles of the fin to the horizontal axis (α1). The four proposed studied cases have the following configurations: Case 1: L1/L = 0.0705 and α1 = 50º; Case 2: L1/L = 0.167 and α1 = 96º; Case 3: L1/L = 0.2635 and α1 = 105º; Case 4: L1/L = 0.363 and α1 = 115º. The results of heat transfer rate between the heat sink and the fresh surrounding flow obtained for the four cases were compared with the original configuration of the commercial sink (Case 5: L1/L = 0.222 and α1 = 80º). For the prediction of fluid dynamic and thermal fields, time-averaged conservation equation of mass, balance of momentum, and conservation of energy were solved with the Finite Volume Method (FVM), more precisely with the commercial code FLUENT (Version 2021 R1). For closure of time-averaged equations, it was used the Reynolds Averaged Navier Stokes (RANS) k – ω SST (Shear Stress Transport) model. It was considered for all simulated cases a turbulent forced convective flow with Reynolds and Prandtl numbers of ReL = 53,000 and Pr = 0.71. Results indicated a difference of nearly 9.0 % in heat transfer rate when the best and the worst configurations were compared. Moreover, the best configuration led to a performance 6.4% superior to the original configuration of the sink, showing that the original configuration of the heat sink can have its design improved.